A New Junction Parameters Determination Using the Double Exponential Model - S. Dib; A. Khoury; F. PéLanchon; P. Mialhe (Active and Passive Electronic Components)
A double exponential model is used to characterize the junction properties of microelectronic devices. A method is developed to extract the physical junction parameters from the current-voltage characteristics. The influence of the start values used for the computing processes are considered and the accuracy is discussed from results of simulated extractions. An experimental test considers the emitter-base junction of bipolar transistors.